2018
DOI: 10.1038/s41591-018-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prenatal anti-Müllerian hormone reprograms the fetus and induces polycystic ovary syndrome in adulthood

Abstract: Polycystic ovary syndrome (PCOS) is the main cause of female infertility worldwide and corresponds with a high degree of comorbidities and economic burden. How PCOS is passed on from one generation to the next is not clear, but it may be a developmental condition. Most women with PCOS exhibit higher levels of circulating luteinizing hormone, suggestive of heightened gonadotropin-releasing hormone (GnRH) release, and Anti-Müllerian Hormone (AMH) as compared to healthy women. Excess AMH in utero may affect the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
362
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(396 citation statements)
references
References 75 publications
(89 reference statements)
21
362
0
13
Order By: Relevance
“…Although null mutation of Amh or Amhr2 is very rare in humans, which limits detailed studies of the potential role of Amh in hippocampal function in patients, a population-based cohort study demonstrated a significant association between Amh single nucleotide polymorphisms and cognitive function parameters in man. 2,4 A recent study in mice demonstrated that Amh in the circulation did not cross the blood-brain barrier, 14 a highly selective barrier operating at birth. 13 However, the source of Amh ligand in the brain requires a thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Although null mutation of Amh or Amhr2 is very rare in humans, which limits detailed studies of the potential role of Amh in hippocampal function in patients, a population-based cohort study demonstrated a significant association between Amh single nucleotide polymorphisms and cognitive function parameters in man. 2,4 A recent study in mice demonstrated that Amh in the circulation did not cross the blood-brain barrier, 14 a highly selective barrier operating at birth. 13 However, the source of Amh ligand in the brain requires a thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Many women are not diagnosed or have long delays before the condition is recognised 2 . Key patient needs are not being met well, and knowledge gaps have been shown in both patients and health professionals alike 2 , 3 . This is of particular concern in a condition where the prevalence is generally considered to be between 9% and 18%, depending on the definition and the population studied 4 …”
mentioning
confidence: 99%
“…Indeed, in addition to gonads, AMHR2 mRNA has recently been localized in rodent and human GnRH neurons, and intracerebroventricular or peripheral injections of AMH in mice were able to increase LH secretion [25, 26]. Furthermore, AMHR2 was identified in rodent pituitary as well as in gonadotrope cells, and AMH was shown to positively regulate FSH [16, 27, 65].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulating evidence shows that AMH contributes to the central control of gonadal functions. The AMH receptor was indeed identified in a significant subset of hypothalamic GnRH neurons in mice and humans, and AMH was found to potently activate the GnRH neuron firing [25, 26]. Amhr2 transcripts and proteins are also present in rat pituitary gland as well as in the gonadotrope cell line LβT2 [16, 27].…”
Section: Introductionmentioning
confidence: 99%